Can C-type natriuretic peptide during in vitro maturation or culture influence the development of bovine embryos? - Rosa, Camila Oliveira; Fontes, Patrícia Kubo [UNESP]; Morotti, Fábio; Costa, Camila Bortoliero; Zangirolamo, Amanda Fonseca; Faustino, Luciana Rocha; Nogueira, Marcelo Fábio Gouveia [UNESP]; Seneda, Marcelo Marcondes (Elsevier, 2024)
The C-type natriuretic peptide (CNP) plays a central role in regulating the meiotic progression of oocytes into growing follicles in mammals. However, there are few reports examining the relationship between CNP and embryonic development. In our study, different concentrations (50, 100, or 150 nM) of CNP were added during in vitro maturation (IVM) of cumulus-oocyte complexes (COCs) or in vitro culture (IVC) of the bovine embryos (B. taurus indicus). The effects on embryo production and transcript abundance of the 20 genes of greatest interest that are related to metabolism, oocyte maturation, follicular development, cell signaling, oxidative and thermal stress, maternal-fetal interaction, and epigenetic regulation were evaluated. The blastocyst rate was influenced by CNP treatment (P = 0.049). Blastocyst rates were 31.05% (136/438) in the control group, 33.47% (162/484) in the 50 nM treatment group, 35.24% (179/508) in the 100 nM treatment group, and 32.53% (162/498) in the 150 nM treatment group for IVM. Furthermore, with IVC CNP supplementation, blastocyst rates were 28.49% (100/351) at 50 nM, 27.67% (119/430) at 100 nM, and 26.92% (112/416) at 150 nM. Moreover, the expression of RE1 silencing transcription factor (REST), a gene related to pluripotency and to embryonic development, was greater (P = 0.028) in response to 150 nM CNP supplementation in IVM. Finally, we observed for the first time the expression of the CNP receptor (NPR2) in embryos and the possible action of CNP at this stage. In conclusion, our data provide a reference for the improvement of IVM results in the in vitro production of bovine embryos with supplementation with 100 nM CNP, and this is the first study to demonstrate the expression of the CNP receptor (NPR2) in bovine embryos.
Keywords: Bovine; CNP supplementation; Embryo; IVM; Meiotic resumption